(-6+12i)(-7-9i)=0

Simple and best practice solution for (-6+12i)(-7-9i)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-6+12i)(-7-9i)=0 equation:


Simplifying
(-6 + 12i)(-7 + -9i) = 0

Multiply (-6 + 12i) * (-7 + -9i)
(-6(-7 + -9i) + 12i * (-7 + -9i)) = 0
((-7 * -6 + -9i * -6) + 12i * (-7 + -9i)) = 0
((42 + 54i) + 12i * (-7 + -9i)) = 0
(42 + 54i + (-7 * 12i + -9i * 12i)) = 0
(42 + 54i + (-84i + -108i2)) = 0

Combine like terms: 54i + -84i = -30i
(42 + -30i + -108i2) = 0

Solving
42 + -30i + -108i2 = 0

Solving for variable 'i'.

Factor out the Greatest Common Factor (GCF), '6'.
6(7 + -5i + -18i2) = 0

Factor a trinomial.
6((1 + -2i)(7 + 9i)) = 0

Ignore the factor 6.

Subproblem 1

Set the factor '(1 + -2i)' equal to zero and attempt to solve: Simplifying 1 + -2i = 0 Solving 1 + -2i = 0 Move all terms containing i to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2i = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2i = 0 + -1 -2i = 0 + -1 Combine like terms: 0 + -1 = -1 -2i = -1 Divide each side by '-2'. i = 0.5 Simplifying i = 0.5

Subproblem 2

Set the factor '(7 + 9i)' equal to zero and attempt to solve: Simplifying 7 + 9i = 0 Solving 7 + 9i = 0 Move all terms containing i to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 9i = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 9i = 0 + -7 9i = 0 + -7 Combine like terms: 0 + -7 = -7 9i = -7 Divide each side by '9'. i = -0.7777777778 Simplifying i = -0.7777777778

Solution

i = {0.5, -0.7777777778}

See similar equations:

| 2x^3-3x=6x^2 | | 6r^2+12r+24=0 | | -(9-6a)-(10+5a)-14=-(2-6a)+(-a)+1 | | -5(n+4)+22=-3n-4 | | 15x-2(x+1)=154 | | 14x-4(4x-2)=5(2x+1)+3 | | 20.00-1.45*v=1.15 | | -9x-156=42-2x | | 14x-3(x+1)=96 | | 53=-16t^2+75t+30 | | 11x+9=4x+5 | | 4x^3+5x=13x^2 | | -[3x-(2x+6)]=-1-[3(2x-4)-3x] | | 8.12x+0.32=3.76x-3.23 | | 14x-3(x+1)=63 | | -10(s+3)=51 | | r^2+2r+4=0 | | y+6-10=0 | | 2/x+6=3/5x-11 | | 3x+3-4x=89 | | -10s+-30=51 | | 3x^3+5x^2=x | | 3.5x=y-7 | | 5.6-0.32*s=1.12 | | 8x+10-9x=89 | | 10.57x-16.75x+17.66=70.84 | | -3m+24-3(m-4)=6m-(4m-5)-2m+1 | | -sin^2x+5cosx=4 | | 4k^2=49 | | Ln(3x-1)=1.5 | | -[8z-(14z+9)]=9+(5z+8) | | 2(x-3)=x-6 |

Equations solver categories